Scientific mapping of Mixed Reality in education: Keyword analysis and bibliographic coupling - Lledó, Gonzalo Lorenzo; Cerdán-Chacón, Andrea; Meliá Beigbeder, Santiago; Lorenzo Lledó, Alejandro (Revista General de Información y Documentación, 2025)
from the incorporation of emerging technologies that enhance learning processes. However, there is a lack of studies that delve into the use of mixed reality in educational settings. Mixed Reality combines the advantages of virtual and augmented reality, making it a promising tool for education. The aim of this research is to analyze trends in the use of Mixed Reality in educational contexts through bibliometric techniques. For this purpose, the Web of Science database and the PRISMA methodology were used, resulting in a final sample of 159 documents. The findings reveal a research line focused on the combined use of Mixed Reality, Augmented Reality, and Virtual Reality in education. Another line focuses on applying Mixed Reality to improve communication and social interaction for students with autism. Key publications such as those by Tang et al. (2020) and Maas and Hughes (2020) have been fundamental in shaping different research areas. It is concluded that there are still areas, such as primary and secondary education, where the use of Mixed Reality has not been explored in depth. As a suggestion for future research, it is recommended to use software tools that allow the analysis of additional qualitative and quantitative indicators related to publications in this field.
Keywords: autism; scientific mapping; mixed reality; bibliographic coupling